2011
DOI: 10.1103/physreva.84.013618
|View full text |Cite
|
Sign up to set email alerts
|

Nonlinear Bose-Einstein-condensate dynamics induced by a harmonic modulation of thes-wave scattering length

Abstract: In a recent experiment, a Bose-Einstein condensate of 7 Li has been excited by a harmonic modulation of the atomic s-wave scattering length via Feshbach resonance. By combining an analytical perturbative approach with extensive numerical simulations, we analyze the emerging nonlinear dynamics of the system on the mean-field Gross-Pitaevskii level at zero temperature. Resulting excitation spectra are presented and prominent nonlinear features are found: mode coupling, higher harmonics generation, and significan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
64
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 48 publications
1
64
0
Order By: Relevance
“…follow from (24), (25) as well as (B1)-(B3) in Appendix B. In order to check how accurate the secondorder EPLT result is, we compare it quantitatively for a 2D square lattice with two other approaches.…”
Section: Higher Order and Numerical Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…follow from (24), (25) as well as (B1)-(B3) in Appendix B. In order to check how accurate the secondorder EPLT result is, we compare it quantitatively for a 2D square lattice with two other approaches.…”
Section: Higher Order and Numerical Resultsmentioning
confidence: 99%
“…For a harmonically trapped Bose-Einstein condensate this induces various phenomena of nonlinear dynamics as, for instance, mode coupling, higher harmonics generation, and significant shifts in the frequencies of collective modes (see, for instance, Ref. [25] and the references therein). Therefore, a periodic modulation of the interaction represents an important new tool for building more versatile quantum simulators.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, it has been shown that Faraday waves can be suppressed in condensates subject either to resonant parametric modulations [12] or space-and time-modulated potentials [13,14], which is a widely studied topic [15][16][17][18][19][20][21][22][23]. Furthermore, in the context of parametric excitations, the formation of density patterns has been studied in expanding ultra-cold Bose gases (either fully [24] or only partially condensed [25,26]), and the spontaneous formation of density waves has been reported for antiferromagnetic BECs [27].…”
Section: Introductionmentioning
confidence: 99%
“…[8], this kind of time-dependent scattering length is capable of producing effects such as higher-harmonic generation and shifts in the frequencies of collective modes. In this paper, we argue that, due to (13), these effects can also be produced by a spatially dependent scattering length.…”
Section: Coupling Modes Due To Feshbach Resonancesmentioning
confidence: 99%
“…In previous approaches, the excitations of such collective modes were usually based on the introduction of time-periodic modulations in system parameters such as the natural frequency of the harmonic trapping potential [1][2][3][4][5][6] and the s-wave scattering length [7,8]. Another possible procedure consists in the introduction of an abrupt change in the potential.…”
Section: Introductionmentioning
confidence: 99%